Safety of Probiotic Supplementation in Preterm Infants with Gastrointestinal Surgical Conditions: A Retrospective Audit - Mohammed Abdul Hakeem; Sanjay Patole; Anthony Keil; Shripada Rao (EL-Med-Pub, 2018)
Background: Limited data exists on the safety of probiotic supplementation in preterm infants with gastrointestinal (GI) surgical conditions. Aims: To assess the safety of Bifidobacterium breve (B. breve) M-16V supplementation in preterm in-fants with GI surgical conditions in our unit with regards to probiotic sepsis. Methods: This retrospective audit of prospectively collected data involved screening of neonatal data-bases to identify preterm infants. Results: Data on 33 preterm infants who underwent 43 GI surgeries and received probiotics was ana-lysed. The median (IQR) gestation at birth and postnatal age at surgery was 30 (26.8-30.7) weeks, and 5 (1-34) days respectively. Twelve (36.3%) infants received probiotics in the preoperative period, 24 (72.7%) received it in the post-operative period, and 10 (30.3%) received it both in the pre-operative and post-operative period. The median (IQR) post-operative age at commencement, duration and number of doses of probiotics was day 10 (6-13), 43 (34-56) days, and 70 (61-100) respectively. Only one infant died; the reason for death was midgut volvulus. None developed Bifidobacterial sepsis. Conclusions: Probiotic sepsis did not occur following B. breve M-16V supplementation in our small cohort of preterm infants with GI surgical conditions. Adequately powered randomised controlled trials are needed to confirm safety and efficacy of B. breve M-16V in this cohort.